Cesarean scar defect: terminological aspects - Sergey A. Martynov; Leyla V. Adamyan (IP Berlin A.V., 2020)
The review aim was to summarize information and to provide terminological analysis of the foreign and Russian literature on assessing the status of the uterine scar after a caesarean section, as well as to identify terms that are most appropriate to use out and during pregnancy, in childbirth and in the postpartum period.